Characterization and diversity of rhizobia nodulating selected tree legumes in Ghana - Boakye, Emmanuel Yaw (Symbiosis, 2016)
The study was conducted to assess the characteristics and diversity of the rhizobia that nodulate some prominent tree legumes in three soils of Ghana. Five introduced and/or indigenous tree legumes were initially assessed for nodulation in three Ghanaian soils. After 12 weeks of growth in nursery pots the 200 rhizobial strains isolated from their nodules were characterized culturally, metabolically and phenotypically. Sixty of these isolates were selected randomly and their genotypic characteristics determined using PCR-RFLP of 16S rRNA and intergenic spacer (ITS) genes. Each tree legume was nodulated by isolates classified as fast or very fast-growers or by isolates classified as slow- or very slow-growers with 54 % of all the 200 isolates belonging to fast- or very fast-growers. Morphologically, eighty five percent of the colonies formed on yeast extract mannitol agar were wet and gummy while 70 % were acid tolerant, i.e. they were able to grow at a pH of 3.5. Combined restriction of the 16S rRNA genes of the 60 rhizobial isolates with five restriction enzymes clearly distinguished seven different clusters at 80 % similarity level. The majority of A. lebbeck isolates were distinct from those of the Acacias and L. leucocephala. The M. thonningii isolates were related to L. leucocephala isolates. Simple PCR of the ITS DNA provided several distinct band sizes indicating great variation among the isolates and restriction of the ITS with three different enzymes did not yield many further differences. Molecular techniques revealed a great diversity among the rhizobia that nodulate tree legumes in the tropics and this may explain why many introduced and/or indigenous trees are able to form nodules with indigenous rhizobia in this region.